DUKUNGAN SOSIAL ORANGTUA, DUKUNGAN SOSIAL TEMAN SEBAYA DAN KECERDASAN EMOSIONAL SEBAGAI PREDIKTOR STRES AKADEMIK SISWA SMK NEGERI 1 KEDUNG - Baskoro Arie Nugroho; Christiana Hari Soetjiningsih; Adi Setiawan (Universitas Paramadina, 2019)
Academic stress can now be found among vocational students, but this can be overcome by facilitating Parental Social Support, Peer Social Support and Emotional Intelligence. The purpose of this study is to prove Parental Social Support, Peer Social Support with Emotional Intelligence as a predictor of Academic Stress. The subjects in this study were 150 students of SMK Negeri 1 Kedung and the method of data collection in this study was psychological scale. Data analysis using multiple linear regression statistical techniques, all calculations using SPSS version 20.0. The results of data analysis obtained the simultaneous value of R between Parental Social Support, Peer Social Support and Emotional Intelligence towards Academic Stress was 0.321 and F value = 12.420 with a significance value of 0.000 (p <0.05). This shows that there is a simultaneous influence between parental social support, peer social support and emotional intelligence on academic stress and also obtained R Square value of 0.103, which means that parental social support, peer social support and emotional intelligence together contribute 10.3% academic stress, the rest is influenced by other factors